TWO NEW RECORDS OF THE GENUS ASTYLUS LAPORTE DE CASTELNAU, 1836 (COLEOPTERA: MELYRIDAE) FOR PERU - Juárez N., Gino (2015)
Two new records for the country are cited: Astylus lojaensis Constantin and Astylus longulus Constantin (Melyridae). Both records were found in the Cuyas cloud forest, an important area of mountain rainforest of the Piura Region.